(untitled) - Chenal, Jonathan (Comptes Rendus. Géoscience, 2025)
Brest and Marseille tide gauges time series between 1885 and 2022 data gaps are filled with data from neighboring tide gauges thanks to a combination model that does not alter original trends. Continuous relative sea level time series obtained from this step are then corrected from the inverse barometer effect and/or periodic components. Time series are systematically explored to form all possible sub-time series, from 20 years length to the full time span, and adjusted with linear and quadratic fits. It is shown that corrections have various effect on parameters best estimates, depending on the chosen period, and that they reduce uncertainties on estimated parameters; corrections schemes comparison and correlation with climate indices suggest the influence of the Northern Atlantic Oscillation on sea level trends and accelerations in both locations. It is shown that linear fit model have less capabilities to represent sea level variability than quadratic fit model. Quadratic fit model shows that Marseille sea level strongly dropped after WWII, with trend of almost 4 mm/yr before this large sea level decrease event, –2 mm/yr during the event, then 3 mm/yr during the recovery following this one, and than Brest sea level did not see such variability. It is shown that sea level extrapolation is consistent with IPCC projections only for interpolation period lengths around 60 years. On this basis, 20 cm additional sea level rise is expected until 2050, and level 50 cm will be reached before the end of 21st century in both Brest and Marseille.